(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2023)
With the increase in global connectivity between people, culture, and cultural patterns, cultural intelligence plays an ever-increasing role in each individual’s life. Whether it is a business, scientific or private field, there is a need for specific competencies related to the possibility of understanding, accepting, and understanding the other, which is more often someone with whom the person does not share cultural heritage, values, or experiences. In order to overcome the barrier that is set up due to the differences above, cultural intelligence is needed. Therefore, this paper deals with the issue of cultural intelligence and aims to show why the issue of cultural intelligence is essential and how to approach it, given the lack of a generally accepted definition of cultural intelligence. The work will present different opinions related to the issue of cultural intelligence and discuss the progress in this field to date.